IMPROVEMENT OF BIOPLASTIC CHARACTERISTICS FROM TAPIOCA WASTE USING TITANIUM DIOXIDE AS A FILLER - Sipayung, Esther Permata; Doloksaribu, Maryati Evivani (EINSTEIN (e-Journal), 2025)
The use of conventional plastics that are difficult to decompose so that the accumulation of plastic waste can cause various problems in the environment. One way to overcome this problem is to replace petroleum-based plastics with other materials that have similar characteristics but are made from renewable materials and have biodegradable properties so that they can decompose naturally in a relatively faster time. Cassava is a polysaccharide containing starch with a high amylopectin content but lower than sticky rice, namely 83% amylopectin and 17% amylose. Tapioca dregs are waste that rots quickly if not processed further. Therefore, efforts are needed to utilize tapioca waste. The addition of Titanium Oxide is very suitable as an antibacterial agent because it is economical, has good mechanical stability, thermal stability, absorbs ultraviolet light, has a photocatalytic effect, and has a large surface area, especially in the manufacture of Bioplastics. Titanium oxide as a filler in bioplastics from tapioca waste can improve the characteristics of bioplastics. In this study, the water resistance value of biodegradable plastics was the highest, namely 47.73%. Titanium Oxide as a filler affects the tensile strength of bioplastics from tapioca waste. The highest tensile stress was obtained at a percentage of 0.8307 MPa, the highest strain was obtained at a percentage of 0.0951%, and the highest modulus of elasticity was 11.4411 MPa. In the biodegradability test with a value of 47.77% with the addition of titanium oxide filler, it meets the requirements to be used as a basic material for biodegradable plastic.